Actividades lúdicas y su incidencia en la enseñanza de la ortografía, quinto grado, escuela "Simón Bolívar", Machala, período 2024-2025 - Marin Reyes, Isaac Piero; Cedillo Ortega, Danna Paola (Machala: Universidad Técnica de Machala, 2025)
This thesis analyzes the impact of ludic (play-based) activities on the teaching of orthography, focusing on fifth-grade students at the “Simón Bolívar” School in the city of Machala, during the 2024–2025 school year. The study is based on the recognition that orthography is a fundamental pillar in the development of linguistic comprehension and that its teaching requires innovative and motivating methods that spark students’ interest. The present research was conducted with the purpose of determining how ludic activities can positively influence the teaching-learning process of orthography, improving academic performance and fostering interest in the correct use of written language. The applied methodology was both qualitative and quantitative, with an explanatory approach, as it seeks to establish the causes and effects of implementing ludic strategies; relational, by analyzing the relationship between the independent and dependent variables; descriptive, by detailing the characteristics of the population and the studied phenomenon; and propositional, by suggesting a pedagogical proposal based on the results obtained. The research modality was both documentary and field-based. A bibliographic review of scientific sources was conducted to support the theoretical framework, and data collection instruments such as surveys for teachers and students, as well as diagnostic tests to assess the level of orthographic knowledge before and after the application of ludic activities, were applied. The population consisted of 84 randomly selected fifth-grade students and 3 teachers from the aforementioned educational institution. The results showed a poor command of orthographic rules, specifically in the use of certain consonants (b/v/d/c/s/z/g/j/ll/y), the application of accent marks, the classification of words according to their stress, and the correct use of punctuation marks. These issues negatively affect the quality of students' written productions and have repercussions on academic performance in subjects that require proper writing skills. However, the implementation of ludic activities proved helpful in improving writing competencies. The study highlights the importance of using ludic activities in teaching orthographic rules and emphasizes the need for a playful pedagogical approach that encourages active participation. Therefore, as a solution, the implementation of an educational blog with a ludic approach is proposed, in which different activities and games aimed at teaching orthographic rules will be presented. The objective of this blog is to strengthen the orthographic skills of students in basic education, leading to an improvement in the correct use of written language. This proposal not only promotes educational innovation but also facilitates the teaching of orthographic rules through a playful and engaging approach. In conclusion, the present research demonstrates that ludic activities have a positive and significant impact on the teaching of orthography, especially in fifth-grade students of basic education. Based on the initial diagnosis, a low level of orthographic competence was identified, which negatively affects the quality of written production and overall academic performance. However, the application of ludic strategies improved students' interest, participation, and orthographic skills, thereby validating the effectiveness of innovative methodologies centered on play and motivation. As a concrete proposal, the implementation of an educational blog with ludic activities aimed at reinforcing proper written language use is suggested, which will contribute not only to the development of linguistic competencies but also to a more interactive, engaging, and effective teaching process.
Esta tesis analiza la incidencia de las actividades lúdicas en la enseñanza de la ortografía, enfocándose en los estudiantes de quinto grado de la escuela “Simón Bolívar” de la ciudad de Machala, período 2024-2025. El estudio parte del reconocimiento de que la ortografía representa un pilar fundamental en el desarrollo de la comprensión lingüística, y que su enseñanza requiere métodos innovadores y motivadores que despierten el interés del estudiante. La presente investigación se realizó con el propósito de determinar cómo las actividades lúdicas pueden influir positivamente en el proceso de enseñanza-aprendizaje de la ortografía, mejorando el rendimiento académico y el interés por el buen uso del lenguaje escrito. La metodología aplicada fue de tipo cualitativa y cuantitativa, con un enfoque explicativo, ya que se busca establecer las causas y efectos de la aplicación de estrategias lúdicas; relacional, al analizar la relación entre las variables independiente y dependiente; descriptivo, al detallar las características de la población y el fenómeno estudiado; y propositivo, al sugerir una propuesta pedagógica fundamentada en los resultados obtenidos. La modalidad de la investigación fue documental y de campo. Se realizó una revisión bibliográfica de fuentes científicas que sustentan el marco teórico y se aplican instrumentos de recolección de datos como encuestas a docentes y estudiantes, así como pruebas diagnósticas para evaluar el nivel de ortografía antes y después de aplicar las actividades lúdicas. La población estuvo conformada por 84 estudiantes de quinto grado escogidos aleatoriamente y 3 docentes del plantel educativo antes mencionado. Los resultados evidenciaron que existe un mal manejo de las normas ortográficas en específico en el uso de determinadas consonantes b/v/d/c/s/z/g/j/ll/y, aplicación de las tildes, clasificación de las palabras según su acento y en el uso correcto de determinados signos de puntuación, lo cual dificulta la calidad de las producciones escritas por parte de los estudiantes, así mismo el problema detectado tendría repercusiones en el rendimiento académico en torno a asignaturas que necesiten un manejo adecuado de la escritura, pero que la implementación de las actividades lúdicas pueden ayudar a mejorar las competencias escritoras. El estudio resalta la importancia del uso de las actividades lúdicas en la enseñanza de las normas ortográficas, de igual forma se destaca la necesidad de aplicar un enfoque pedagógico lúdico que incentive la participación. Por ello se propone como solución la implementación de un blog educativo con un enfoque lúdico en el cual se presentaran diferentes actividades y juegos que enseñen las normas ortográficas siendo el fin de este blog fortalecer las habilidades ortográficas de los estudiantes de educación general básica, para lograr una mejora en el uso correcto del lenguaje escrito, el cual no solo fomentara la innovación educativa si no que facilitara la enseñanza de las normas ortográficas mediante un enfoque lúdico. En conclusión, la presente investigación demuestra que las actividades lúdicas tienen un impacto positivo y significativo en la enseñanza de la ortografía, especialmente en estudiantes de quinto grado de educación general básica. A partir del diagnóstico inicial se evidencio un bajo dominio de las normas ortográficas, lo cual afecta negativamente la calidad de las producciones escritas y el rendimiento académico en general. Sin embargo, la aplicación de estrategias lúdicas permitió mejorar el interés, la participación y las habilidades ortográficas de los estudiantes, validando así la efectividad de metodologías innovadoras centradas en el juego y la motivación. Como propuesta concreta, se plantea la implementación de un blog educativo con actividades lúdicas orientadas a reforzar el uso correcto del lenguaje escrito, lo que no solo contribuirá al desarrollo de competencias lingüísticas sino también a una enseñanza más interactiva, atractiva y eficaz.
Keywords: ORTOGRAFÍA; ACTIVIDADES LÚDICAS; ENSEÑANZA-APRENDIZAJE; EDUCACIÓN BÁSICA; ESTRATEGIAS METODOLÓGICAS; MOTIVACIÓN